Comparison of stress analysis for dental crown (FPD) for various materials. (2021) - Jayakumar, N.; Senthilkumar, G.; Aravinda Samy, S.; Karthick, V.; Renganathan, T.
Abstract: Dental crown is used to defend uncertain teeth (from decaying) or restoring a damaged tooth or severely worn tooth. Crown is the portion of the teeth above the gum line. The reason for this examination is to gauge the failure risk and stress analysis of the crown for different ceramic materials such as zirconia and yttrium stabilized zirconia to help dentists to choose a better ceramic crown. Fixed prosthesis dentures are used as alternative sources for dental implants. FPD dental rebuilding efforts, likewise alluded to as circuitous reclamations, incorporate crowns, span (fixed false teeth), decorate, on lays, and facade. Fixed prosthodontics can be utilized to reestablish single or different teeth, traversing territories where teeth have been lost. As a rule, the primary favorable circumstances of fixed prosthodontics when contrasted with direct rebuilding efforts are the unrivaled quality when utilized in enormous reclamations, and the capacity to make a stylish looking tooth. Similarly, as with any dental reclamation, standards used to decide the proper rebuilding includes thought of the materials to be handled, degree of tooth obliteration, direction and area of tooth, and state of adjoining teeth. In this study three types of biocompatible materials are used to find the material that suits the Fixed Partial Denture with low Maximum principal stress.